Employment and rebellion in conflicted and fragile states - Michael J. Gilligan (IZA World of Labor, 2016)
In addition to the heart-breaking human costs, violent civil rebellion is a cause of chronic economic under-development. Employment programs with former combatants and at-risk youth have improved their livelihoods, but not their support for non-violence and respect for law. Rebel groups provide security and social benefits that formal employment does not offer, possibly making switching out of rebellion into formal employment unappealing. However, a jobs program that addressed the psycho-social motivations to join rebel groups resulted in significant reductions in crime and violence. This is an important step forward in our understanding of how to lure people away from violent rebellion.
Keywords: J46; O10; O19; 330; civil war; peacebuilding; fragile states; unemployment; violence